Analysis of water leached from soil treated with leachate from plant biomass ash Análise da água lixiviada do solo tratado com lixiviação de cinzas de biomassa vegetal - Fernandes M. (2017)
© 2017, Institute for Environmental Research in Hydrographic Basins (IPABHi). All rights reserved.This work analyzed water leached from soil treated with leachate from plant biomass ash. The ash was generated by industrial boilers used in the pulp and paper industry. Experiments were carried out in columns filled with soil, and the ash was then added to the soil to simulate field conditions. The ash was applied at 30 and 60 tons per hectare rate. The simulated rainwater was prepared for three scenarios: pH 3.0, 6.5 and 8.0. Each leaching experiment simulated an annual precipitation of 2,045 mm. The results showed that the parameter that demands more attention is aluminum concentration. In this context, in acidic conditions (pH 3.0) and with a significant amount of ash added (60 tons per hectare), the level of aluminum may reach the maximum level for drinking water. Despite the potential impact of aluminum, the use of ash from plant biomass in soil for agricultural purposes may serve as an alternative strategy for disposal of this waste.